Flexibility in ad hoc networks - Forde, Timothy Kirby (Trinity College (Dublin, Ireland). Department of Electronic & Electrical Engineering, 2005)
This thesis represents a step forward in our understanding of what flexibility, adaptability and reconfigurability means at the network-layer of mobile, wireless, ad hoc networks. Mobile, wireless, ad hoc networks are collections of autonomous routers that have the ability to dynamically and rapidly form networks without the use of any centralised network infrastructure using wireless communication technologies. Ad hoc routing protocols are at the core of enabling ad hoc networks as they allow remote nodes to communicate without resorting to primitive flooding techniques. Ad hoc networks, by their nature, will experience divergent user scenarios and networking conditions that demand routing protocols which are tailored to their requirements. However, to date, the static configuration of one routing protocol across the entire network has been the norm. This thesis argues that such a rigid approach constrains the temporally and spatially divergent nature of the system. This thesis shows that a more flexible approach to the design of the network-layer for mobile wireless ad hoc networks is both necessary and feasible. The thesis explores the need for such flexibility in ad hoc networks and presents an enabling system in the form of a novel network-layer which incorporates multiple routing protocols.
Keywords: Electronic and Electrical Engineering, Ph.D.; Ph.D. Trinity College Dublin